Total Plate Count Analysis and Food-Contaminating Bacterial Identification of Smoked Tatihu (Thunnus albacares) Sold in Several Traditional Markets in Ambon, Indonesia - Haurissa, Evangelista Risalia; Yunita, Melda; Sulfiana, Sulfiana (Folia Medica Indonesiana, 2024)
Highlights: 1. This research provides important information regarding the food safety of smoked tatihu (yellowfin tuna) sold in several traditional markets in Ambon, Indonesia. 2. We find that smoked tatihu fish samples examined at 2 of 3 traditional markets in Ambon city are unsafe for consumption according to the Indonesian National Standard due to bacterial contamination. 3. The findings indicate that smoked fish can be contaminated by Gram-positive bacteria, such as Staphylococcus gallinarum, Staphylococcus sciuri, Rothia kristinae, and Staphylococcus pseudintermedius. Abstract The large marine area and abundant fish resources of Maluku Province, Indonesia, are in contrast to the poor hygiene of its traditional markets, which can cause microbial contamination and taint processed products, such as smoked tatihu (yellowfin tuna). In Ambon city, Maluku, Indonesia, no research had been conducted concerning total plate count analysis and food-contaminating bacterial identification that could guarantee the microbiological safety of smoked tatihu. Therefore, this study aimed to assess the microbiological quality of smoked tatihu according to Indonesian National Standards (INS 2725:2013) and to identify any presence of food-contaminating bacteria. This research was a quantitative descriptive study with a true experimental laboratory approach. The samples used were smoked tatihu collected from three traditional markets in Ambon, Indonesia. The spread plate method was used in the isolation process, while the total plate count analysis was performed to estimate the quantity of colonies on each petri dish. Bacterial identification was carried out macroscopically and microscopically. The microscopic identification involved Gram staining to determine the shape and color of the bacteria. Additionally, the bioMérieux VITEK 2 Compact system was utilized for biochemical identification to ascertain the species of bacteria present. The results revealed that the colony counts in smoked tatihu from the Mardika market and Hative Kecil market were 1.1 x 104 CFU/g and 8.2 x 106 CFU/g, respectively. However, smoked tatihu from the Batu Meja market had an excessive number of colonies that were difficult to quantify. The contaminating bacteria were identified as Staphylococcus gallinarum, Staphylococcus sciuri, Rothia kristinae, and Staphylococcus pseudintermedius. In conclusion, smoked tatihu fish from the Mardika market are considered safe for consumption as the microbiological parameters do not exceed the Indonesian National Standards, whereas those obtained from the Hative Kecil and Batu Meja markets are unsafe for consumption due to the excessive presence of food-contaminating bacteria.